Comparative study of Southeast Asian Kitabs (2): papers on tasawwuf and fatwa texts presented at the Sophia University Workshop on May 20, 2012 - Comparative... (Institute of Asian Cultures-Center for Islamic Studies, Sophia University, 2014)
st,1/nr,c.1